## Solving the Equation (m+2)(m+3) = (m+2)(m-2)

This equation presents a quadratic equation that we can solve to find the values of *m*. Here's how we can approach it:

### 1. Expand the Equation

First, expand both sides of the equation by using the distributive property or FOIL method:

**Left side:**(m+2)(m+3) = m² + 5m + 6**Right side:**(m+2)(m-2) = m² - 4

Now, our equation becomes: m² + 5m + 6 = m² - 4

### 2. Simplify the Equation

Since both sides have an m² term, we can subtract m² from both sides, simplifying the equation:

5m + 6 = -4

### 3. Isolate the Variable

To isolate 'm', we need to get rid of the constant term (6). Subtract 6 from both sides:

5m = -10

### 4. Solve for 'm'

Finally, divide both sides by 5 to find the value of 'm':

m = -2

### Conclusion

Therefore, the solution to the equation (m+2)(m+3) = (m+2)(m-2) is **m = -2**.